Human resource managers’ development of understanding on the concept of work engagement - Telma Dís Ólafsdóttir 1990- (2017)
The individual employee aims for an enjoyable workplace environment as on average much of their lifetime is spent working. At the same time most organizations expect their employees to work hard, deliver high quality performance, be energetic, and dedicated towards their work. Many concepts have tried to focus on how employees’ health can affect their performance. One of those is a relatively new concept in the literature, called work engagement (Macey & Schneider, 2008). In the past decade there has been a rise in scientific studies on the concept. Work engagement however is a concept that has usually been measured at the individual level (Harter, Schmidt & Hayes, 2002). In this paper the concept will be looked at from the perspective of human resource management, or unit level. Human resource managers within a company are in the position to try to affect employees’ work engagement. Somewhat fewer researches exist on the concept on the unit level and here in Iceland on the concept in general. The objective of the research was to examine the position of the concept of work engagement among human resource managers in companies that in one way or another are related to the tourism industry in Iceland. That is, where in the development of understanding the concept the human resource managers are positioned. First they need to be aware of the concept existence and then have knowledge of what the concept entails. Then they need to reflect on what practices they have or could have which can result with them systematically applying the concept. The findings of the study reveal that generally the concept of work engagement has received attention of quite a few human resource managers within the tourism business in Iceland. Understanding on the concept was in general good, although how far along in the application process varied. However, difference between human resource managers how far along they are in their development of understanding seems to be related to two awareness issues. On one hand how they ...